The patient-level effect of the cost of Cancer care - financial burden in German Cancer patients - Mehlis, Katja; Apostolidis, Leonidas; Jäger, Dirk; Winkler, Eva C. (BMC cancer, 2020)
Financial toxicity of cancer has so far been discussed primarily in the US health care system and is associated with higher morbidity and mortality. In European health care systems, the socio-economic impact of cancer is poorly understood. This study investigates the financial burden and patient-reported outcomes of neuroendocrine (NET) or colorectal (CRC) cancer patients at a German Comprehensive Cancer Center.
Gesehen am 18.08.2020